The influence of mass media and political attitudes on students' political participation in the 2020 regent election at SMA Negeri 2 Raha, - Fajar Maulana, Harry (Universitas Ahmad Dahlan, 2022)
Purpose of this study is to explain the influence of mass media and political attitudes on students' political participation in the 2020 regent election at SMA Negeri 2 Raha, Muna Regency. . The method used in this research is associative quantitative research with ex post facto descriptive approach. The research sample is 26 respondents. Data collection techniques using questionnaires and data analysis techniques using regression. Based on the results of the analysis and hypothesis testing, it shows that there is an influence of mass media and political attitudes on student political participation in the 2020 regent election at SMA Negeri 2 Raha Muna Regency of 58.8%, therefore students must always be given directions in every election. so that students participate in elections